Estrutura de comunidades de formigas em savanas arbóreas tropicais: um teste da generalidade de padrões ecológicos contrastando Brasil e Austrália - Campos, Ricardo Ildefonso de (2009)
The aim of this study was to compare ant community structure between the savannas of Brazil and Australia. The study was conducted in woodland savanna areas nearby Darwin, in northern Australia, and Uberlândia and Caldas Novas in central Brazil. The sampling design consisted of eight 400 m line transects, four in each continent, with eight pitfall traps and four baits located on and around each of 20 trees evenly spaced along each transect. Ant richness and species turnover were compared at three spatial scales: pitfalls associated with a tree, trees within a transect, and transects within a savanna. The composition of the Australian and Brazilian savanna ant faunas was broadly similar at the sub-family level, despite the very low proportion of shared genera and species. Overall ant abundance was almost three times higher in Australia than in Brazil, both on the ground and on vegetation, but overall species richness was higher in Brazil (150 species) than in Australia (93). Species richness was similar at very small (pitfall trap) scales, but was increasingly higher in Brazil with increasing spatial scale. In the Australian savanna and, to a lower extent, in the Brazilian savanna the ant assemblage from the trees was a nested subset of the ground ant assemblage. However, while in Australia there was a positive relationship between tree and ground ant abundance, but not for ant richness, the same relationship was found for ant richness, but not for ant abundance, in the Brazilian savanna. Interspecific competition was relatively more important for the ant community structure of the Australian savanna than for the Brazilian savannas, regardless of the nesting/foraging stratum. Also, interspecific competition was relatively more important in structuring soil than compared to the tree assemblages. Finally it was found that there were greater ant richness, abundance and dominance at nitrogen-rich baits than at carbohydrate-rich baits for both soil and tree ant assemblages. My study revealed scale-dependent differences in species richness and species turnover for savanna ant assemblages in Australia and Brazil. This further underlines the importance of biogeographical context when analyzing ant communities and also highlights the importance of processes acting at regional scales in determining species richness in ant communities. I also concluded that interspecific competition is an important force in structuring the savanna ant community but other factors such as evolutionary history, habitat preferences and stochastic events may also play an important role in the organization of the savanna ant community.